2015
DOI: 10.1093/europace/euv288
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K antagonist oral anticoagulants in atrial fibrillation accompanying mitral stenosis: the concept for a trial

Abstract: Patients at thromboembolic risk with non-valvular atrial fibrillation (AF) can now be managed either with a vitamin K antagonist (VKA) or with a fixed dose of a non-VKA oral anticoagulant (NOAC), while patients with valvular AF have been restricted to VKAs on the basis of a potentially higher risk and different mechanism of thrombosis, and the lack of sufficient data on the efficacy of NOACs. The terms 'non-valvular AF' and 'valvular AF' have not been however consistently defined. 'Valvular' AF has included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 50 publications
(45 reference statements)
0
21
0
1
Order By: Relevance
“…Also, EHRA type 1 is broadly similar to the previously described mechanical and rheumatic mitral valvular AF (MARM-AF). 444…”
Section: Af With Associated Valvular Heart Diseasementioning
confidence: 99%
“…Also, EHRA type 1 is broadly similar to the previously described mechanical and rheumatic mitral valvular AF (MARM-AF). 444…”
Section: Af With Associated Valvular Heart Diseasementioning
confidence: 99%
“…[21] In patients with rheumatic MS, low cardiac output with reduced transmitral flow has been implicated as a potential mechanism for increased rate of thrombus formation. [5], [22] In a study of 1544 patients with severe MS by Mahmood and colleagues, LA thrombus was identified by transesophageal echocardiogram (TEE) in 55.7% (161/289) of patients with AF and 10.2% (128/1255) of patients without AF. [23] The finding that 1 in 10 patients in the non-AF group had LA thrombus further supports the concept that rheumatic mitral valve disease may contribute to LA thrombus formation regardless of the underlying cardiac rhythm.…”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…comparing NOACs to the standards of care for thromboembolic prophylaxis (antiplatelet agents or VKA) in patients with mitral stenosis. 39 They claim that a randomized, open-label, superiority trial should be conducted in specific countries with a high prevalence of mitral stenosis using a NOAC available for once daily use (rivaroxaban or edoxaban) to facilitate patients' compliance, at the same dosage used in pivotal trials in AF. The overall sample size would vary depending on the expected stroke rate, the study duration and the expected hazard ratio of stroke reduction, from around 600 to 7000.…”
Section: Accepted Manuscriptmentioning
confidence: 99%